Identification of passion fruit oil adulteration by chemometric analysis of FTIR spectra - Kiefer, Johannes; Lampe, Anja I.; Nicoli, Stefano F.; Lucarini, Massimo; Durazzo, Alessandra (Molecules, 2019)
It is frequently diluted with sunflower oil. Sunflower oil is also a potential adulterant as its addition does not notably alter the appearance of the passion fruit oil. In this paper, we show that this is also true for the FTIR spectrum. However, the chemometric analysis of the data changes this situation. Principal component analysis (PCA) enables not only the straightforward discrimination of pure passion fruit oil and adulterated samples but also the unambiguous classification of passion fruit oil products from five different manufacturers. Even small amounts—significantly below 1%—of the adulterant can be detected. Furthermore, partial least-squares regression (PLSR) facilitates the quantification of the amount of sunflower oil added to the passion fruit oil. The results demonstrate that the combination of FTIR spectroscopy and chemometric data analysis is a very powerful tool to analyze passion fruit oil.
CRIS-Team Scopus Importer:2019-09-17
Keywords: Chemometrics; Infrared spectroscopy; Maracuja oil; Passion fruit oil; Principal component analysis